Southward movement of ITCZ and consequent second maximum of rainfall over the southern parts of west coast of India - MUKHERJEE, A. K.; PADMANABHAM , K. P.; KRISHNAVENI, K. B. (MAUSAM, 1978)
African southwest monsoon is explained in terms of ITCZ. Different zones of rainfall regime with reference to the position of the ITCZ can be worked out. In some parts of West Africa, there are two maxima of rainfall and they are explained by the northward and southward journey of the ITCZ. Similar double maxima are found in southern parts of west coast of India. ITCZ during its northward journey cannot be properly identified Over India. But it is possible to identify the ITCZ during its southward journey. A study of the rainfall pattern on the west coast of India has been made to show that the second maximum of rainfall over Kerala is not due to the onset of northeast monsoon but due to the southward journey of the ITCZ.